2000
DOI: 10.1029/1999rs002238
|View full text |Cite
|
Sign up to set email alerts
|

A discussion on the variations of MST/ST radar echo power with an atmospheric layer resolved by frequency domain interferometry technique

Abstract: Abstract. The relationship between an atmospheric layer and its VHF backscatter resolved by the frequency domain interferometry (FDI) technique is investigated in this article. A theoretical expression connecting the radar echo power with the thickness and position of an atmospheric layer and the range weighting function of a matched filter is derived. It shows that the farther the layer locates from the central height of the radar volume, the weaker the echo power will be. This feature is attributed to the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Similar method was also employed by Brown and Fraser [1996] and Luce et al [2001] in their multiple–frequency observations. However, Chen and Chu [2000] suggested that the relationship between echo power and FDI layer position can also be applied to reveal the FDI phase bias under the situation of single layer in the radar volume. In addition, Palmer et al [2001] and Chilson et al [2001] considered the initial phases of the carrier frequencies and measured them from the signals that were leaked from the transmitted signals back to the receiver by an ultrasonic delay line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar method was also employed by Brown and Fraser [1996] and Luce et al [2001] in their multiple–frequency observations. However, Chen and Chu [2000] suggested that the relationship between echo power and FDI layer position can also be applied to reveal the FDI phase bias under the situation of single layer in the radar volume. In addition, Palmer et al [2001] and Chilson et al [2001] considered the initial phases of the carrier frequencies and measured them from the signals that were leaked from the transmitted signals back to the receiver by an ultrasonic delay line.…”
Section: Introductionmentioning
confidence: 99%
“…We indeed found systematic bias in the FDI phase. Moreover, phase calibration using the condition of a single layer in the radar volume, which was implemented by Chen and Chu [2000], is one application of echo power. We will demonstrate that the condition of single layer can be released in using the relationship between echo power and FDI phase.…”
Section: Introductionmentioning
confidence: 99%
“…Three co-located atmospheric radars on the campus of National Central University (24.97 • N, 121.18 • E) were employed in the campaign experiment for the wind velocity measurements and comparisons, i.e., 52 MHz Chung-Li VHF radar, 449 MHz wind profiler, and 1290 MHz wind profiler. The Chung-Li VHF radar is a teaching and research facility that can not only measure atmospheric wind velocity, turbulence, precipitation, lightning, meteor trail, and wave phenomena in the troposphere and/or mesosphere, but also can detect the echoes from ionospheric field-aligned irregularities at Bragg scale to study the plasma irregularities and ionospheric dynamics in the E and F regions [32][33][34][35][36]. The Chung-Li VHF radar is equipped with three phased-array antennas with a total area of 0.9 hectares; they are a strato-and troposphere (ST) array, ionospheric array, and interferometry array.…”
Section: Experimental Setup and Data Analysismentioning
confidence: 99%